The Role of Technology-Based Customer Relationship Management in Sustainable Competitive Advantage - A Field Study of Iraqi Banks - Sabah Alchalabi*, Alzahraa; Hammood Chitheer, Saadoon (Journal of Economics and Administrative Sciences, 2024)
The objective of this research is to examine the impact of technology-based Customer Relationship Management (CRM) on sustainable competitive advantage in government and private banks in Baghdad. The research problem is summarized by the main question: “Have bank leaderships been able to leverage technology-based CRM for sustainable competitive advantage? And have they been able to maximize this impact?” Given the significance of the banking sector, government and private banks in Baghdad were chosen as the focus of this research. Commercial and Islamic banks were selected for the study, and the researcher conducted field visits to six banks (including Rafidain Bank, Trade Bank of Iraq, Alnahrain Islamic Bank, Al Taif Islamic Bank, Iraqi Middle East Investment Bank, and National Bank of Iraq). The research sample comprises 212 frontline employees, and the researchers employed a descriptive-analytical approach. A questionnaire was used as the primary data collection tool for the field study, consisting of 60 items covering the research variables and their sub-dimensions. Interviews were also conducted. After evaluating and testing the reliability and validity of the research measurement tools, the data were analyzed and hypotheses were tested using appropriate statistical tools, including the SPSS for data analysis. The results revealed a significant and meaningful impact of technology-based CRM on sustainable competitive advantage.  Paper Type: Research Paper